Bacteriome of Moist Smokeless Tobacco Products Consumed in India With Emphasis on the Predictive Functional Potential - Sajid, Mohammad; Srivastava, Sonal; Kumar, Amit; Kumar, Anuj; Singh, Harpreet; Bharadwaj, Mausumi (Frontiers in Microbiology, 2021)
Smokeless tobacco products (STPs) carry assorted microbial population that contributes to carcinogens synthesis like tobacco-specific nitrosamines (TSNAs). Extensive exploration of microbiota-harbouring STPs is required to understand their full carcinogenic potential. Here, we applied 16S rRNA gene sequencing to investigate bacteriome present in moist STPs immensely consumed in India (Khaini, Moist-snuff, Qiwam, Snus). Further, the functional metagenome was speculated by PICRUSt (Phylogenetic Investigation of Communities by Reconstruction of Unobserved States) to assign the abundance of genes related to nitrogen metabolism, bacterial toxins, antibiotic drug resistance and other pro-inflammatory molecules. Highly diverse bacterial communities were observed in all moist STPs. Taxonomic analysis revealed a total of 549 genera belonging to four major phyla Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria. Overall, the core bacterial genera Acinetobacter, Bacillus, Prevotella, Acetobacter, Lactobacillus, Paracoccus, Flavobacterium and Bacteroides were significantly abundant in moist STPs. Elevated moisture-holding products like Moist-snuff and Qiwam harbour rich bacterial species diversity and showed similar bacteriome composition. Furthermore, Qiwam products showed the highest level of genes associated with nitrogen metabolism, antibiotic resistance, toxins, and pro-inflammation (predicted by PICRUSt) which can contribute to the synthesis of TSNAs and induction of oral cancer. The present broad investigation of moist STPs-associated bacteriome prevalence and their detailed metabolic potential will provide novel insight into the oral carcinogenesis induced by STPs.